The impact of earlier flood recession on metacommunity diversity of wintering waterbirds at shallow lakes in the middle and lower Yangtze River floodplain - Zhenhua Wei; Lizhi Zhou (Avian Research, 2023)
The hydrological regime in wetlands plays an important role in the process of wintering waterbird metacommunity assemblage. However, increasing frequency of extreme climate and the intensification of human activities, such as the construction of sluices and dams, have resulted in frequently abnormal hydrological regime in the middle and lower Yangtze River floodplain. In recent years, earlier flood recession has become one of the main hydrological problems faced in the shallow lakes, having a great impact on wetland biodiversity. It is necessary to understand the impact of earlier flood recession on waterbirds, an indicator of wetland biodiversity, and the metacommunity concept is helpful to elucidate the underlying mechanism involved in the processes of assemblage by waterbird communities. In this study, we surveyed the wintering waterbirds at three sub-lakes of Caizi Lakes during 2019–2020 and 2020–2021 and compared the richness, abundance, alpha and beta diversity of waterbirds in and among local metacommunities under earlier flood recession and normal hydrological regime . The results showed that the earlier flood recession reduced the species richness in the early stage and abundance in the late stage, it also reduced the Shannon–Wiener index in the early stage and increased the dissimilarity between and within waterbird metacommunities in the late stage. The partition of beta diversity showed that the turnover component played a major role in the process of waterbird metacommunity assemblage. It was found that the earlier flood recession reduced the richness, abundance in different stages of flood recession, which also increased the turnover of waterbirds. Metacommunities with high habitat heterogeneity had better resistance to abnormal hydrological regime, which resulted in high dissimilarity between and within metacommunities. The results of this study provide important information for waterbird conservation and water level management at shallow lakes in the middle and lower Yangtze River floodplain.